2007
DOI: 10.1149/1.2792338
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Spray Pyrolysis Deposition and Characterization of Tantalum–Aluminum Oxide Thin Films

Abstract: Tantalum oxide and tantalum-aluminum oxide films have been prepared by pyrosol using alcoholic start solution of tantalum chloride and aluminum acetylacetonate at substrates temperatures of 250°C. All films are amorphous independent of the deposition conditions. X-ray diffraction shows that aluminum incorporation in deposited materials stabilizes the amorphous phase even after annealing at 525°C and 900°C. Energy dispersive spectroscopy, Rutherford backscattering, refractive index, and FTIR results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Al x Ta y O z mixture thin films have previously been grown by several methods including sol‐gel,35 spray pyrolysis,36 radiofrequency (RF) sputtering,37, 38 and CVD 39, 40. The dielectric properties achieved with the Al x Ta y O z mixtures were between those of Al 2 O 3 and Ta 2 O 5 35–39. In addition, Hara et al40 showed that Al x Ta y O z mixture films prepared by CVD onto Pt and Si are highly stable in strong acid and alkali solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Al x Ta y O z mixture thin films have previously been grown by several methods including sol‐gel,35 spray pyrolysis,36 radiofrequency (RF) sputtering,37, 38 and CVD 39, 40. The dielectric properties achieved with the Al x Ta y O z mixtures were between those of Al 2 O 3 and Ta 2 O 5 35–39. In addition, Hara et al40 showed that Al x Ta y O z mixture films prepared by CVD onto Pt and Si are highly stable in strong acid and alkali solutions.…”
Section: Introductionmentioning
confidence: 99%